Spotlights on adult patients with pediatric-type diffuse gliomas in accordance with the 2021 WHO classification of CNS tumors - Chen, Wenlin; Jin, Shanmu; Liu, Qianshu; Wang, Hai; Xia, Yu; Guo, Xiaopeng; Guo, Siying; Wang, Yaning; Shi, Yixin; Liu, Delin; Li, Yilin; Wang, Yuekun; et al. (Frontiers in Neuroscience, 2023)
Introduction The fifth edition of the World Health Organization (WHO) classification of central nervous system (CNS) tumors released in 2021 formally defines pediatric-type diffuse gliomas. However, there is still little understanding of pediatric-type diffuse gliomas, and even less attention has been paid to adult patients. Therefore, this study describes the clinical radiological, survival, and molecular features of adult patients with pediatric-type glioma. Methods Adult patients who underwent surgery from January 2011 to January 2022, classified as pediatric-type glioma, were included in this study. Clinical, radiological, histopathological, molecular pathological, and survival data were collected for analysis. Results Among 596 adult patients, 20 patients with pediatric-type glioma were screened, including 6 with diffuse astrocytoma, MYB- or MYBL1-altered, 2 with diffuse midline glioma, H3 K27-altered, and 12 with diffuse pediatric-type high-grade glioma, H3-wildtype and IDH-wildtype. Pediatric high-grade glioma (pHGG) frequently showed tumor enhancement, peritumoral edema, and intratumoral necrosis. Adult patients with pHGG showed a longer life expectancy than adult patients with glioblastoma. Common molecular alterations included chromosome alterations and CDKN2A/B, PIK3CA, and PTEN, while altered KMT5B and MET were found to affect the overall survival. Conclusion Our study demonstrated adult patients with pediatric-type glioma. Notably, our research aims to expand the current understanding of adult patients with pediatric-type diffuse gliomas. Furthermore, personalized therapies consisting of targeted molecular inhibitors for MET and VEGFA may exhibit beneficial effects in the corresponding population.